Die gleichnisreden Jesu - Jülicher, Adolf, 1857-1938 (Freiburg I.B. Leipzig [etc.] J.C.B. Mohr (P. Siebeck), 1899)
Australian-born chef Chris Honor has been hailed by Giles Coren of The Times as 'a nailed-on culinary genius', running 'the most rewarding small local restaurant I have encountered in years'. His recipes for great salads, sweet and savory bakes, soups and wonderful sharing plates are highly original, but really simple to create at home, and with American food writer Laura Washburn Hutton he shares 100 of his most memorable recipes.
1.t. Die gleichnisreden Jesu in allgemeinen. 2., neu bearb. aufl.--2.t. Auslegung der gleichnisreden der drei ersten evangelien.
Mode of access: Internet.
Keywords: Jesus Christ -- Parables; Parables; Parables; Parables